Minimally invasive aortic arch surgery: Early and late outcomes. (September 2017) - Risteski, Petar; El-Sayed Ahmad, Ali; Monsefi, Nadejda; Papadopoulos, Nestoras; Radacki, Isabel; Herrmann, Eva; Moritz, Anton; Zierer, Andreas
Abstract: Background: We analyzed our experience with the aortic arch operations performed through a minimally invasive approach, with emphasis on safety and feasibility, early and late outcomes. Material and methods: We reviewed the medical records of 71 adult patients with aortic arch aneurysm (58, 82%), dissection (10, 14%) or porcelain aorta (3, 4%) who underwent primary arch surgery through a partial upper sternotomy. Results: The aortic arch was replaced partially in 45 (63%), or totally in 26 (37%) patients. The repair was further extended with the elephant trunk procedure, conventional in 8 (11.3%) or frozen in 15 (21.1%) patients. No conversion to full sternotomy was needed. New permanent renal failure occurred in 1 (1.4%), temporary neurologic deficit in 2 (2.8%) and permanent neurologic deficit in 3 (4.2%) patients. Early mortality was observed in 4 (5.6%) patients. Actuarial survival was 79.2 ± 8.3% at 4 years and cumulative reoperation-free survival was 76.4 ± 9.4% at 4 years. Conclusion: Minimally invasive aortic arch surgery is safe and feasible. Early outcomes are at the lower range compared to other published series. Late outcomes are not adversely influenced, as the desired extent of aortic resection can be achieved, producing a durable aortic repair. Highlights: The technique of minimally invasive aortic arch surgery through partial upper sternotomy is described. Early morbidity and mortality are at the lower range compared to published conventional series. Late outcomes are not adversely influenced by the less invasive approach.